Association between immune check point inhibitors and digestive system inflammatory adverse reactions: evidence from pharmacovigilance analysis and systematic review - Zou, Ya; Li, Qinchuan; Zhou, Lu; Lu, Yun; Wei, Hua; Zhou, Yan; Lin, Shibo; Guo, Xirui; Yan, Shihao; Wang, Hongju; Xie, Fangqing; Liu, Chun; et al. (Frontiers in Pharmacology, 2025)
PurposeComparative real-world data on the spectrum of digestive inflammatory adverse reactions across ICI classes are limited. Existing evidence on immune-related Sjögren’s syndrome/sialadenitis consists largely of case reports and small series.MethodsWe performed disproportionality analysis using the FDA Adverse Event Reporting System (FAERS) database (2015–2023) to evaluate associations between ICIs and digestive inflammatory adverse reactions. Additionally, we conducted a systematic review up to July 2025 to identify published cases of ICI-associated Sjögren’s syndrome/sialadenitis.ResultsPD-1 inhibitors (pembrolizumab and nivolumab) showed the strongest associations with immune-mediated oesophagitis and gastritis. Pembrolizumab was also highly associated with hepatobiliary events, including immune-mediated cholangitis (ROR 249.18, 95% CI 169.04-367.32) and hepatitis (ROR 85.51, 95% CI 73.22-99.86). In contrast, the CTLA-4 inhibitor ipilimumab exhibited the strongest signal for immune-mediated enterocolitis. Atezolizumab and ipilimumab were significantly associated with spontaneous bacterial peritonitis. Our systematic review identified 93 cases of ICI-associated Sjögren’s syndrome/sialadenitis, predominantly in patients with melanoma or lung cancer receiving PD-1 inhibitors.ConclusionPD-1 inhibitors are more strongly associated with upper GI and hepatobiliary inflammatory adverse reactions, whereas CTLA-4 inhibitors carry a higher risk of enterocolitis. These findings underscore the need for ICI-specific monitoring protocols. Early recognition and tailored management—including potential treatment interruption or corticosteroid use—are critical to minimizing severe outcomes. Clinicians should maintain a high index of suspicion for rare inflammatory adverse reactions such as sialadenitis, even as incidence remains low. These insights support more personalized risk-benefit assessment and inflammatory adverse reactions management in patients receiving ICIs.